Examining persuasive message type to encourage staying at home during the COVID-19 pandemic and social lockdown: A randomized controlled study in Japan - Okuhara, Tsuyoshi (Patient Educ Couns, 2020)
OBJECTIVE: Behavioral change is the only prevention against the COVID-19 pandemic until vaccines become available. This is the first study to examine the most persuasive message type in terms of narrator difference in encouraging people to stay at home during the COVID-19 pandemic and social lockdown. METHODS: Participants (n = 1,980) were randomly assigned to five intervention messages (from a governor, a public health expert, a physician, a patient, and a resident of an outbreak area) and a control message. Intention to stay at home before and after reading messages was assessed. A one-way ANOVA with Tukey’s or Games–Howell test was conducted. RESULTS: Compared with other messages, the message from a physician significantly increased participants’ intention to stay at home in areas with high numbers of people infected (versus a governor, p = .002; an expert, p = .023; a resident, p = .004). CONCLUSION: The message from a physician―which conveyed the crisis of overwhelmed hospitals and consequent risk of people being unable to receive treatment―increased the intent to stay at home the most. PRACTICE IMPLICATIONS: Health professionals and media operatives may be able to encourage people to stay at home by disseminating the physicians’ messages through media and the internet.